The emerging role of histone deacetylase 1 in allergic diseases - Wang, Yongfang; Wang, Huiying (Frontiers in Immunology, 2022)
Histone deacetylase 1 (HDAC1) is a unique member of the classes I HDACs and helps to regulate acute and chronic adaptation to environmental stimuli such as allergen, stress. Allergic diseases are complex diseases resulting from the effect of multiple genetic and interacting foreign substances. Epigenetics play an important role in both pathological and immunomodulatory conditions of allergic diseases. To be consistent with this role, recent evidence strongly suggests that histone deacetylase 1 (HDAC1) plays a critical role in allergic response. HDAC1 expression is stimulated by allergen and attributes to increase T helper 2(Th2) cytokine levels, decrease Th1/ Th17 cells and anti-inflammatory cytokine Interleukin-10(IL-10), and TWIK-related potassium channel-1(Trek-1) expression. This review focuses on the contribution of HDAC1 and the regulatory role in characterizing allergic endotypes with common molecular pathways and understanding allergic multimorbidity relationships, as well as addressing their potential as therapeutic targets for these conditions.